2009
DOI: 10.1177/0093854809351682
|View full text |Cite
|
Sign up to set email alerts
|

Job Involvement, Job Stress, Job Satisfaction, and Organizational Commitment and the Burnout of Correctional Staff

Abstract: In an era in which rising costs, shrinking budgets, and personnel shortages are common, it is increasingly important to provide a positive work situation to ensure worker stability. Research indicates that job burnout is a negative response that is harmful to the employee and to the organization. Depersonalization, emotional exhaustion, and feeling a lack of accomplishment at work are all dimensions of job burnout. This study examined the association of job involvement, job stress, job satisfaction, and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
249
6
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(286 citation statements)
references
References 50 publications
13
249
6
10
Order By: Relevance
“…Lambert, Hogan and Barton (2002) refer to it as an individual subjective feeling, which reflects whether the needs of a person are being met, or not, by a given assignment/job. These authors are corroborated by Griffin, Hogan, Lambert, Tucker-Gail and Baker (2010) who evoke Spector (1996Spector ( /2003, essentially defining job satisfaction as how much people like their jobs. Yoon and Thye (2002) consider that it can be construed as a sort of positive emotion that directs the organization.…”
Section: Job Satisfactionmentioning
confidence: 87%
“…Lambert, Hogan and Barton (2002) refer to it as an individual subjective feeling, which reflects whether the needs of a person are being met, or not, by a given assignment/job. These authors are corroborated by Griffin, Hogan, Lambert, Tucker-Gail and Baker (2010) who evoke Spector (1996Spector ( /2003, essentially defining job satisfaction as how much people like their jobs. Yoon and Thye (2002) consider that it can be construed as a sort of positive emotion that directs the organization.…”
Section: Job Satisfactionmentioning
confidence: 87%
“…For example, the work and organisational psychology literature has highlighted how staff perceptions of social climate are associated with work outcomes such as staff productivity, job performance, and work stress. Studies have shown that staff perceptions of a workplace climate correlate significantly with negative employee attitudes (e.g., the intent to leave a job) and levels of job satisfaction (Ulrich et al 2007), psychological wellbeing (Garrett & McDaniel 2001), stress and burnout (Griffin et al 2010;Lambert et al 2006), and motivation and job performance (Parker et al 2003). The connection between social climate and staff absenteeism has also been widely documented.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
“…Research conducted in forensic mental health settings has often focussed on the connection between social climate and treatment outcomes; in other words, how the perception of the social environment impacts upon patient care (Clarke et al 2002a;Gelade & Ivery 2003;Griffin et al 2010;Kangis et al 2000;Langdon et al 2004;Langdon et al 2006;Moos & Bromet 1978;Pritchard & Karasick 1973). One study by Arnetz and Arnetz (2001) found that fear of violence experienced by health care staff was negatively and significantly related to patientreported quality of care.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
“…Research also has indicated that a relationship exists between job satisfaction and organizational commitment [38][39][40]. Organizational commitment involves individual employees' psychological attachment to the organization for which they work and therefore is a strong indicator of performance in the workplace [36].…”
Section: Variables Impacting Work-life Balancementioning
confidence: 99%